Air particulate pollution in Kuala Lumpur - A statistical consideration - Mohd. Yusoff, Mohd. Rashid (1988)
The 24-h average concentrations of inhalable (IPM) and total suspended particulate (TSP) matter collected at one site of Kuala Lumpur were studied. Both IPM and TSP were highly correlated (r = 0.81) with a positive intercept on the TSP axis which clearly indicates that the IPM constitutes a portion of the TSP concentration. The impact of meteorology parameter such as wind speed and rainfall on the particulate concentrations using a simple linear regression analysis are also discussed in thi paper.